Peran Unit Aviation Security Untuk Menunjang Keamanan Dan Keselamatan Penerbangan Jamaah Haji Di Bandar Udara Internasional Adi Soemarmo Boyolali - Riko Hanggara; Yulia Aji Puspitasari (Institut Nalanda, 2023)
Air transportation plays an important role in the flight of pilgrims. One of the providers of operational places for the transportation of pilgrims is Adi Soemarmo Boyolali International Airport which serves Central Java and DIY. In the flight process of pilgrims, one of the units that plays an important role is the Aviation Security unit. The purpose of this research is to analyze the role and work system of the Aviation Security Unit during the Hajj pilgrimage at Adi Soemarmo Boyolali International Airport. This research is a qualitative research using primary and secondary data types. Data collection techniques in this study used the interview method, the observation method and the documentation method at the Aviation Security unit at Adi Soemarmo Boyolali International Airport during the 2022 hajj pilgrimage. The results of this study indicate that the Aviation Security unit plays an important role in supporting the security and safety of pilgrims' flights at Adi Soemarmo Boyolali International Airport. The work system at the Aviation Security unit at Adi Soemarmo Boyolali International Airport has been organized in such a way that it uses a shift work system. AVSEC officers will be on standby 24 hours to serve both inspections and other matters in accordance with regulations and Standard Operating Procedures to support the security and safety of prospective pilgrims.